Finding brain oscillations with power dependencies in neuroimaging data - Dähne, S.; Nikulin, V. V.; Ramírez, D.; Schreier, P. J.; Müller, K.-R.; Haufe, S. (NeuroImage)
Phase synchronization among neuronal oscillations within the same frequency band has been hypothesized to be a major mechanism for communication between different brain areas. On the other hand, cross-frequency com- munications are more flexible allowing interactions between oscillations with different frequencies. Among such cross-frequency interactions amplitude-to-amplitude interactions are of a special interest as they show how the strength of spatial synchronization in different neuronal populations relates to each other during a given task. While, previously, amplitude-to-amplitude correlations were studied primarily on the sensor level, we present a source separation approach using spatial filters which maximize the correlation between the envelopes of brain oscillations recorded with electro-/magnetoencephalography (EEG/MEG) or intracranial multichannel re- cordings. Our approach, which is called canonical source power correlation analysis (cSPoC), is thereby capable of extracting genuine brain oscillations solely based on their assumed coupling behavior even when the signal-to- noise ratio of the signals is low. In addition to using cSPoC for the analysis of cross-frequency interactions in the same subject, we show that it can also be utilized for studying amplitude dynamics of neuronal oscillations across subjects. We assess the performance of cSPoC in simulations as well as in three distinctively different analysis sce- narios of real EEG data, each involving several subjects. In the simulations, cSPoC outperforms unsupervised state-of-the-art approaches. In the analysis of real EEG recordings, we demonstrate excellent unsupervised dis- covery of meaningful power-to-power couplings, within as well as across subjects and frequency bands.

Detecting Directionality in Random Fields Using the Monogenic Signal - Olhede, S. C.; Ramírez, D.; Schreier, P. J. (IEEE Trans.\ Inform.\ Theory)
Detecting and analyzing directional structures in images is important in many applications since one-dimensional patterns often correspond to important features such as object contours or trajectories. Classifying a structure as directional or non-directional requires a measure to quantify the degree of directionality and a threshold, which needs to be chosen based on the statistics of the image. In order to do this, we model the image as a random field. So far, little research has been performed on analyzing directionality in random fields. In this paper, we propose a measure to quantify the degree of directionality based on the random monogenic signal, which enables a unique decomposition of a 2D signal into local amplitude, local orientation, and local phase. We investigate the second-order statistical properties of the monogenic signal for isotropic, anisotropic, and unidirectional random fields. We analyze our measure of directionality for finite-size sample images, and determine a threshold to distinguish between unidirectional and non-unidirectional random fields, which allows the automatic classification of images.

A Quadratically Convergent Method for Interference Alignment in MIMO Interference Channels - Lameiro, Christian; Santamaría, Ignacio (IEEE Signal Process. Lett.)
Alternating minimization and steepest descent are commonly used strategies to obtain interference alignment (IA) solutions in the $K$-user multiple-input multiple-output (MIMO) interference channel (IC). Although these algorithms are shown to converge monotonically, they experience a poor convergence rate, requiring an enormous amount of iterations which substantially increases with the size of the scenario. To alleviate this drawback, in this letter we resort to the Gauss-Newton (GN) method, which is well-known to experience quadratic convergence when the iterates are sufficiently close to the optimum. We discuss the convergence properties of the proposed GN algorithm and provide several numerical examples showing that it always converges to the optimum with quadratic rate, reducing dramatically the required computation time in comparison to other algorithms, hence paving a new way for the design of IA algorithms.

Interference-Temperature Limit for Cognitive Radio Networks with MIMO Primary Users - Lameiro, Christian; Utschick, Wolfgang; Santamaría, Ignacio (Proc.\ Asilomar Conf.\ Signals Syst.\ Computers)
This paper derives the interference-temperature (IT) limit for a multi-antenna primary user (PU) with a rate constraint. While in the case of a single-antenna PU there is a one-to-one mapping between IT and achievable rate, this correspondence does not hold anymore when a multiple-input multiple-output (MIMO) system is considered. In such cases, the spatial distribution of the interference must be taken into account, since it strongly affects the PU performance. To this end, we derive a closed-form expression for the maximum IT that can be tolerated by identifying the worst-case interference covariance matrix, which results in a multilevel waterfilling problem.

A Regularized Maximum Likelihood Estimator for the Period of a Cyclostationary Process - Ramírez, D.; Schreier, P. J.; Vía, J.; Santamaría, I.; Scharf, L. L. (Proc.\ Asilomar Conf.\ Signals Syst.\ Computers)
We derive an estimator of the cycle period of a univariate cyclostationary process based on an information- theoretic criterion. Transforming the univariate cyclostationary process into a vector-valued wide-sense stationary process allows us to obtain the structure of the covariance matrix, which is block-Toeplitz, and its block size depends on the unknown cycle period. Therefore, we sweep the block size and obtain the ML estimate of the covariance matrix, required for the information- theoretic criterion. Since there are no closed-form ML estimates of block-Toeplitz matrices, we asymptotically approximate them as block-circulant. Finally, some numerical examples show the good performance of the proposed estimator.

Optimization and estimation of complex-valued signals - Adali, Tulay; Schreier, Peter J. (IEEE Signal Processing Magazine)
Complex-valued signals occur in many areas of science and engineering and are thus of fundamental interest. When developing signal processing methods in the complex domain, there are two key issues: making use of the full statistical information and optimization. In this article, we review the necessary tools to address these two key issues and provide examples in filtering and blind source separation (BSS) that utilize these tools.

Interference Shaping Constraints for Underlay MIMO Interference Channels - Lameiro, Christian; Santamaría, Ignacio; Utschick, Wolfgang (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

A lower bound for the Fisher information measure - Stein, Manuel; Mezghani, Amine; Nossek, Josef A. (IEEE Signal Process.\ Lett.)

Efficient algorithm for optimizing data-pattern tomography - Motka, L.; Stoklasa, B.; Rehacek, J.; Hradil, Z.; Karasek, V.; Mogilevtsev, D.; Harder, G.; Silberhorn, Christine; Sánchez-Soto, L. L. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Cloud - Alpsancar, Suzana (Ortsregister)

Design of Highly Porous Single‐Site Catalysts through Two‐Step Postsynthetic Modification of Mixed‐Linker MIL‐53(Al) - Gotthardt, Meike A.; Schoch, Roland; Brunner, Tobias S.; Bauer, Matthias; Kleist, Wolfgang (ChemPlusChem)
Keywords: General Chemistry

Synthesis and characterization of bimetallic metal–organic framework Cu–Ru-BTC with HKUST-1 structure - Gotthardt, Meike A.; Schoch, Roland; Wolf, Silke; Bauer, Matthias; Kleist, Wolfgang (Dalton Transactions)
A mixed-metal framework Cu–Ru-BTC with the formula Cu2.75Ru0.25(BTC)2·xH2O was successfully synthesized. Partial substitution of Cu2+ by Ru3+ in the paddlewheel structure was proven using X-ray absorption spectroscopy.
Keywords: Inorganic Chemistry

A Rhodium Triphenylphosphine Catalyst for Alkene Hydrogenation Supported on Neat Superparamagnetic Iron Oxide Nanoparticles - Dehe, Daniel; Wang, Lei; Müller, Melanie K.; Dörr, Gunder; Zhou, Zhou; Klupp-Taylor, Robin N.; Sun, Yu; Ernst, Stefan; Hartmann, Martin; Bauer, Matthias; Thiel, Werner R. (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Hydrolytic Stability and Hydrogen Peroxide Activation of Zirconium‐Based Oxoclusters - Faccioli, Francesco; Bauer, Matthias; Pedron, Danilo; Sorarù, Antonio; Carraro, Mauro; Gross, Silvia (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry

Base‐Free Non‐Noble‐Metal‐Catalyzed Hydrogen Generation from Formic Acid: Scope and Mechanistic Insights - Mellmann, Dörthe; Barsch, Enrico; Bauer, Matthias; Grabow, Kathleen; Boddien, Albert; Kammer, Anja; Sponholz, Peter; Bentrup, Ursula; Jackstell, Ralf; Junge, Henrik; Laurenczy, Gábor; Ludwig, Ralf; et al. (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

The Electronic Ground State of [Fe(CO)3(NO)]−: A Spectroscopic and Theoretical Study - Klein, Johannes E. M. N.; Miehlich, Burkhard; Holzwarth, Michael S.; Bauer, Matthias; Milek, Magdalena; Khusniyarov, Marat M.; Knizia, Gerald; Werner, Hans-Joachim; Plietker, Bernd (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

A series of amide functionalized isoreticular metal organic frameworks - Keceli, E.; Hemgesberg, M.; Grünker, R.; Bon, V.; Wilhelm, C.; Philippi, T.; Schoch, Roland; Sun, Y.; Bauer, Matthias; Ernst, S.; Kaskel, S.; Thiel, Werner R. (Microporous and Mesoporous Materials)
Keywords: Mechanics of Materials; Condensed Matter Physics; General Materials Science; General Chemistry

A Catalytic System for the Activation of Diorganozinc Reagents - Werner, Thomas; Bauer, Matthias; Riahi, Abdol Majid; Schramm, Heiko (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Polynuclear Iron(II)–Aminotriazole Spincrossover Complexes (Polymers) In Solution - Bräunlich, Irene; Sánchez-Ferrer, Antoni; Bauer, Matthias; Schepper, Rahel; Knüsel, Philippe; Dshemuchadse, Julia; Mezzenga, Raffaele; Caseri, Walter (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

HERFD-XAS and valence-to-core-XES: new tools to push the limits in research with hard X-rays? - Bauer, Matthias (Phys. Chem. Chem. Phys.)
This perspective accounts for the benefits of the high resolution hard X-ray spectroscopic methods HERFD-XANES and valence-to-core-XES.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy